Secure data collection in telemonitoring autonomous vehicle - Wibowo, Marcellinus Hendro Adi (2017)
In an autonomous vehicle system, a secure communication between vehicles and instruments is critical. Particularly, in a metro or underground communication system, the communication is done through a Supervisory Control and Data Acquisition (SCADA) network system which is purely wired system. This wired system does not include any wireless connections; hence an outsider attack is very unlikely to happen. Then Gin, this does not imply that the system is safe from attack as an attack could come from insider by sending more command or less command. This attack can be detected by comparing the features extracted from the traffic happening to the heuristic and proper data set. The comparison done is not only by comparing the distribution of the data transferred but also as looking at the correlation between each instrument. The correlation is needed since several instruments might work dependently while others might work independently. Data that are compared in the analysis are the features from of each instrument from the traffic which are number of command transfer, number of handshake transfer, and the ratio of command transferred to the command transfer median from the samples. These three features are then analyzed and the results will show whether there’s an anomaly in certain period.